Pemanfaatan Media Pembelajaran Interaktif Berbasis Aplikasi Plotagon dalam Pembelajaran Keterampilan Berbicara Bahasa Arab - Fini Adila Kurnia; Risda Aprilia; Habibullah Muhammad; Laily Fitriani (Akademika : Jurnal Teknologi Pendidikan, 2023)
This research aims to make a major contribution to achieving the ability to speak Arabic by utilizing interactive learning media through Plotagon application for UIN Maulana Malik Ibrahim Malang students. This research method uses a qualitative approach with a case study type of research. In this study, the population used was 49 students from the faculty of medicine and health sciences, first semester of class D in the pharmacy study program, and the sample taken was 30% of the total population, namely 15 students. The data collection techniques in this research are through observation, in-depth interviews, and documentation. Then analyze the data using the Miles and Huberman model by carrying out data reduction, data presentation and data verification or drawing conclusions. The accuracy of the researcher's data uses triangulation techniques of source, time, researcher, theory and data collection methods. The results of this research are that digital-based learning media through animated videos created with the Plotagon application as a medium for learning Arabic speaking skills has a positive and significant impact where learning in class becomes communicative and students are more active in practicing speaking with their fellow students. Plotagon application-based learning media in learning Arabic speaking skills with positive and effective achievements. So that this media can support the achievement of maharah al-kalam learning objectives as evidenced by their ability to communicate, express simple sentences and create active and creative learning and the learning objectives can be achieved optimally.